ANALISIS ASPEK TEKNIS DAN FINANSIAL USAHA PERIKANAN BAGAN APUNG (LIFT NET) DI OHOI SELAYAR KABUPATEN MALUKU TENGGARA - Christy Agathys Notanubun; Willem Talakua; Stevanus Marelly Siahainenia (Universitas Pattimura, 2021)
The utilization rate of small pelagic fish in Fish Management Area-714 was moderate exploited. Utilization of small pelagic fish uses several fishing tools, one of which is a lift net. There are 27 floating charts (lift net) on Ohoi Selayar, consisting of 12 boat-lift net businesses and 15 raft-lift net businesses which differ in construction. The purpose of this research is to describe the technical conditions and to analyze the financial condition of the lift net fishery business. The research method is a survey method, with primary and secondary data collection. Sampling was using purposive sampling method. Data analysis was descriptive qualitative and descriptive quantitative. The results showed that the technical aspects of the lift net include: the construction size of the raft-lift net 14.8 m x 13.6 m and the boat-lift net 23.2 m x 24 m. The construction parts are the counterweight, the lift net housing, the support posts, the net rollers, the anchor railings. The auxiliary components consist of: nets, lighting devices, bodies and transport machines and embankments. The method of operating a lift net includes: preparation to fishing ground, setting, immersing, hauling and sorting. The number of fishing activities for the raft-lift net averaged 180 trips/year and the boat-lift net 182 trips/year. Based on the criteria of financial ratio analysis with a non-time value of money (R/C and PP) approach, it can be concluded that the business of the raft-lift net and boat-lift net at the research location is financially feasible to develop.